Analisis Superstruktur Wacana Stand Up Comedy Academy Sebagai Bahan Ajar Pembelajaran Bahasa Indonesia Sekolah Menengah Atas Kelas X - Rahayu, Pradita Lara Puji, Drs. Agus Budi Wahyudi, M.Hum (2017)
This study has three objectives: (1) Describe the structure of the text stand up comedy academy. (2) Identify the form of text structure discourse academy stand-up comedy. (3) Presenting the results of research analyzes the discourse superstructure stand up comedy academy as teaching materials learning Indonesian high school class X. This study is qualitative descriptive. The data in this study a full text. The source of the data in this study is an online website that is youtube. Data collection techniques in this study using techniques of documentation. Analysis of the data using a unified method, which is a unified referential decisive tool in the form of the referent. The results of this study, there are three things. 1) Discourse stand up comedy academy have the same structure, which is based on the genre of discourse. 2) Scheme and the order of discourse stand up comedy academy in accordance with the text anecdotes that have components that abstract structure, orientation, crisis, reaction and coda. The division of the structure can be divided into two parts, namely the complete structure da incomplete. 3) implementation of the results of this study can be used as teaching material in high school class X on producing text anecdotes, reports on the results of observation, complex procedures, and a coherent negotiating text in accordance with the characteristics that made verbally or in writing.